Suara dari masa silam : Teori dan metode sejarah lisan / Paul Thompson ; penerjemah, Windu W. Yusuf ; penyunting, M. Nursam. - THOMPSON, Paul, 1935-; Windu W. Yusuf; Nursam, M. (Ombak, 2012)
x, 331 hlm. : ilus. ; 21 cm (3 eks.)